2010
DOI: 10.1111/j.1461-0248.2010.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Driven to distraction: detecting the hidden costs of flea parasitism through foraging behaviour in gerbils

Abstract: Gerbilline rodents such as Allenby's gerbils (Gerbillus andersoni allenbyi), when parasitized by fleas such as Synosternus cleopatrae pyramidis, devote long hours of grooming to remove the ectoparasites. Yet no detrimental energetic or immunological effects of the ectoparasites have been found in adult Allenby's gerbil. Why should gerbils go to such trouble? We tested for the various ways that fleas can negatively affect gerbils by manipulating flea infestation on gerbils and the presence of a fox. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…v www.esajournals.org There is growing evidence that ectoparasites can have significant negative impacts on the physiology of individual hosts, and the vital rates of host populations (Hawlena et al 2006a, Hawlena et al 2006b, Devevey et al 2008, Devevey and Christe 2009, Pfäffle et al 2009, Kam et al 2010. Therefore, it is conceivable that lowered ectoparasite loads in burned forest contribute to high post-fire deer mouse abundance, e.g., through effects on body condition (Hawlena et al 2006a, Devevey et al 2008, Devevey and Christe 2009 or feeding behavior (Scantlebury et al 2007, Raveh et al 2011), which in turn influences reproductive output of deer mice. Intriguingly, Raveh et al (2011) showed that flea-infested rodents were less vigilant and v www.esajournals.org had higher giving-up densities (i.e., tended to quit foraging at higher densities of food remaining in the patch).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…v www.esajournals.org There is growing evidence that ectoparasites can have significant negative impacts on the physiology of individual hosts, and the vital rates of host populations (Hawlena et al 2006a, Hawlena et al 2006b, Devevey et al 2008, Devevey and Christe 2009, Pfäffle et al 2009, Kam et al 2010. Therefore, it is conceivable that lowered ectoparasite loads in burned forest contribute to high post-fire deer mouse abundance, e.g., through effects on body condition (Hawlena et al 2006a, Devevey et al 2008, Devevey and Christe 2009 or feeding behavior (Scantlebury et al 2007, Raveh et al 2011), which in turn influences reproductive output of deer mice. Intriguingly, Raveh et al (2011) showed that flea-infested rodents were less vigilant and v www.esajournals.org had higher giving-up densities (i.e., tended to quit foraging at higher densities of food remaining in the patch).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is conceivable that lowered ectoparasite loads in burned forest contribute to high post-fire deer mouse abundance, e.g., through effects on body condition (Hawlena et al 2006a, Devevey et al 2008, Devevey and Christe 2009 or feeding behavior (Scantlebury et al 2007, Raveh et al 2011), which in turn influences reproductive output of deer mice. Intriguingly, Raveh et al (2011) showed that flea-infested rodents were less vigilant and v www.esajournals.org had higher giving-up densities (i.e., tended to quit foraging at higher densities of food remaining in the patch). In our previous research (Zwolak et al 2012), we found that deer mice in unburned forest had higher giving-up densities than mice from burned forest, but the reason for this difference was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Apprehension can be defined as a reduction in attention devoted to performing an activity (foraging) as a consequence of reallocating attention to detecting or responding to predators or competitors (Dall et al 2001;Kotler et al 2002Kotler et al , 2004Kotler et al , 2010Raveh et al 2011). Apprehensive foraging allows a forager to harvest (or handle) food while increasing its alertness to predators.…”
mentioning
confidence: 99%
“…An example of such a study is the effect of parasites and the distraction they produce on the risk-taking behavior in gerbils (e.g. Raveh et al, 2011).…”
Section: Current Applicationsmentioning
confidence: 99%